Analysis of the Involvement of the Isoleucine Biosynthesis Pathway in Photoheterotrophic Metabolism of Rhodospirillum rubrum - Bayon-Vicente, Guillaume; Marchand, Elie; Ducrotois, Jeson; Dufrasne, François E.; Hallez, Regis; Wattiez, Ruddy; Leroy, Baptiste (Frontiers in Microbiology, 2021)
Purple non sulphur bacteria (PNSB) are recognised as highly versatile group of bacteria that assimilate a broad range of carbon source. Growing heterotrophically, PNSB such as Rhodospirillum rubrum, generate reduced equivalents that are used for biomass production. However, under photoheterotrophic conditions, more reduced electron carriers than required to produce biomass are generated. The excess of reduced equivalents still needs to be oxidised for the metabolism to optimally operate. These metabolic reactions are known as electron sinks. Most PNSB rely on CO2-fixing Calvin cycle to oxidise those reduced equivalents. Besides CO2 fixation, H2 and polyhydroxyalkanoate production also represent electron sink used by PNSB. In addition to these well described electron sinks, the involvement of some pathways in redox poise is still controversial and requires further studies. Among them, the isoleucine biosynthesis has been recently highlighted as one of these potential pathways. Here, we explore the role of isoleucine biosynthesis in Rhodospirillum rubrum. Our results demonstrate that the isoleucine content is higher under illuminated conditions and that submitting Rhodospirillum rubrum to a light stress further increases this phenomenon. Moreover, we explore the (p)ppGpp production in Rs. rubrum and its potential link with light stress. We further demonstrated that a fully functional isoleucine biosynthesis pathway is mandatory for the onset of Rhodospirillum rubrum growth under photoheterotrophic conditions even in presence of exogenous isoleucine source. Altogether, our data suggest that isoleucine biosynthesis could play a key role in redox homeostasis.